Theirs but to do and die?: guaranteeing soldiers' right to life - Watkins, Richard (2017)
On 25 October 1855 Lord Cardigan led the Light Brigade in a fateful charge against a Russian artillery battery. Poet Laureate Lord Tennyson immortalised the cavalry’s valour in verse.